INTERVENSI KEPERAWATAN UNTUK MENGURANGI STRES HOSPITALISASAI PADA ANAK USIA PRA SEKOLAH DI RUMAH SAKIT STELLA MARIS MAKASSAR - Mery Sambo (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
Hospitalization of a child is a process in planning or emergency reason requires the child to stay in the hospital, to undergo therapy and care until the child can be discharged back home. During the process, children can experience various events in the form of a very traumatic experience and full of stress. Playing can reduce the anxiety in children due to hospitalization. One type of game that can reduce the anxiety is playing a puzzle. This study aimed to determine the effect of playing therapy on anxiety of preschool children during hospitalization. This research used quantitative pre experimental design method with one group pre-test-post test design. Sampling technique used a consecutive sampling with the number of respondents 20 persons. Data were collected using questionnaires. Data analysis was used a Wilcoxon statistic test with 95% significance level (? = 0,05). Wilcoxon test results found p = 0.000 indicates there was influence of playing puzzle therapy to the anxiety of children who dipercitalisasi.